High entropy alloy nanocomposites produced by high pressure torsion. (15th April 2021) - Taheriniya, Shabnam; Davani, Farnaz A.; Hilke, Sven; Hepp, Marco; Gadelmeier, Christian; Chellali, Mohammed Reda; Boll, Torben; Rösner, Harald; Peterlechner, Martin; Gammer, Christoph; Divinski, Sergiy V.; Butz, Benjamin; et al.
Abstract: High-pressure torsion was applied to join two disks of single-phase equiatomic fcc CoCrFeMnNi and bcc HfNbTaTiZr high entropy alloys (HEAs). After 15 revolutions a bulk nanocomposite had developed with alternating nano-lamellae of elongated nanocrystalline CoCrFeMnNi and mixed amorphous-nanocrystalline HfNbTaTiZr, exhibiting complex microstructures with numerous vortex-like regions. While the fcc phase retains a rather homogeneous elemental distribution, the former bcc high entropy alloy experiences a chemical separation towards Ta-rich and Ta-poor phases. The joining of dissimilar HEAs under constrained conditions (cold shut) enables the design of novel HEA-based composites by non-equilibrium processing. Graphical abstract: Image, graphical abstract